2017
DOI: 10.1111/add.13774
|View full text |Cite
|
Sign up to set email alerts
|

Substance use disorders and the risk of suicide mortality among men and women in the US Veterans Health Administration

Abstract: Current substance use disorders (SUDs) signal increased suicide risk, especially among women, and may be important markers to consider including in suicide risk assessment strategies. None the less, other co-occurring psychiatric disorders may partially explain associations between SUDs and suicide, as well as the observed excess suicide risk associated with SUDs among women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
150
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 226 publications
(167 citation statements)
references
References 26 publications
(27 reference statements)
16
150
0
1
Order By: Relevance
“…In this nested case–control study performed in a large French cohort of PLHIV in the cART era, we found that most factors associated with suicide mortality among PLHIV were similar to those of the general population . Not having children and psychological morbidity such as active or substituted drug consumption, alcohol intake > 20 g/day or a history of abuse, a history of depressive disorder and/or of attempted suicide, and intake of psychotropic drugs were significantly associated with death by suicide, whereas age, gender, country of birth, positive HCV serology and HIV‐related factors, such as AIDS status, use of cART, nadir and current CD4 counts and HIV viral load, were not found to be associated with an increased risk of suicide.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In this nested case–control study performed in a large French cohort of PLHIV in the cART era, we found that most factors associated with suicide mortality among PLHIV were similar to those of the general population . Not having children and psychological morbidity such as active or substituted drug consumption, alcohol intake > 20 g/day or a history of abuse, a history of depressive disorder and/or of attempted suicide, and intake of psychotropic drugs were significantly associated with death by suicide, whereas age, gender, country of birth, positive HCV serology and HIV‐related factors, such as AIDS status, use of cART, nadir and current CD4 counts and HIV viral load, were not found to be associated with an increased risk of suicide.…”
Section: Discussionmentioning
confidence: 78%
“…In the general population, severe mental illness and substance use disorders have previously been associated with excess suicide mortality . In a British cohort of 18 201 patients with severe mental illness, the age‐ and sex‐standardized mortality ratio for suicide was seven‐fold higher than in the general population .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This provides food for thought that the lack of adequate treatment modalities might lead to societal exclusion, and even criminalization, of this group [6]. This leads to an extremely problematic situation, as there is apparently lack of attention from scholars, clinical agencies, donors and governmental-funded bodies to invest in the development and adaptation of evidence-based treatment modalities for this group.…”
Section: Intellectually Disabled and Addicted: A Call For Evidence Bamentioning
confidence: 99%
“…Opioids, a class of drugs that includes both illicit substances (e.g., heroin) and prescription medications (e.g., morphine, oxycodone, and codeine), account for over 2.5 million substance use disorders in the United States every year (American Society of Addiction Medicine [ASAM, ]) and resulted in over 33,000 overdose deaths in 2015 and 34,000 in 2016 (ASAM, ). In addition, although individuals with substance use disorders in general have been found to exhibit a 54% increase in risk for death by suicide (Bohnert, Ilgen, Louzon, McCarthy, & Katz, ; Poorolajal, Haghtalab, Farhadi, & Darvishi, ; Schneider, ), there is increasing evidence that opioid use disorders in particular are associated with heightened suicidal ideation, suicide attempts, and completed suicide (Ashrafioun, Bishop, Conner, & Pigeon, ; Bohnert et al., ; Kuramoto, Chilcoat, Ko, & Martins, ; Wilcox, Conner, & Caine, ). For example, it is estimated that 32–48% of opioid‐dependent individuals attempt suicide at least once (Roy, ; Trémeau et al., ), and individuals who seek treatment for opioid dependence are 13.5 times more likely to die by suicide than the general population (Wilcox et al., ).…”
mentioning
confidence: 99%